Incidence of perioperative sleep-disordered breathing in patients undergoing major surgery: a prospective cohort study - Roggenbach, Jens; Saur, Patrick; Hofer, Stefan; Bruckner, Thomas; Preusch, Michael; Carbone, Remo; Walther, Andreas (Patient safety in surgery, 2014)
Major surgery might have a modulating effect on nocturnal breathing patterns. The incidence and course of perioperative sleep-disordered breathing in individuals without a previous diagnosis of obstructive sleep apnea has not been investigated sufficiently so far.
Gesehen am 10.11.2020